Fe/Fe3C decorated 3-D porous nitrogen-doped graphene as a cathode material for rechargeable Li–O2 batteries. (10th February 2016) - Lai, Yanqing; Chen, Wei; Zhang, Zhian; Qu, Yaohui; Gan, Yongqing; Li, Jie
Graphical abstract: Fe/Fe3 C decorated 3-D porous N-doped graphene are prepaed by a one-step carbonization process, with MOF as the structure-directing agent. The method provides a simple and scalable route for preparing 3-D porous graphene materials.The as-prepared material possesses an excellent bi-functional electrocatalytic activity. While applied as the cathode materials of Li–O2 batteries, the cell exihibits high capacity and considerable rate capability. Highlights: A facile simple strategy is employed to in-situ fabricate Fe/Fe3 C decorated 3-D porous nitrogen-doped graphene. MIL-100(Fe), a kind of metal-organic framework, is proved playing a structure-directing role in this advanced synthesis route. This material possesses excellent bi-functional electro-catalytic activity for ORR and OER and shows good electrochemical performance while used as cathode material for Li–O2 batteries. The MOF-assisted synthesis method would be a promising new strategy for the synthesis of 3-D porous graphene materials. Abstract: Fe/Fe3 C decorated 3-D porous N-doped graphene (F-PNG) is designed and synthesized via a one-step carbonization route. During the process, MIL-100(Fe), a kind of metal organic frameworks (MOFs) plays a structure-directing role. It is found that F-PNG with 3-D porous structure is constituted by N-doped graphene and extremely small Fe/Fe3 C particles uniformly distribute on the surface of graphene. This rationally designed F-PNG possesses excellent oxygen reduction reaction and oxygen evolution reaction bifunctional electrocatalytic activity. While the material is explored as a cathode of Li–O2 batteries, it exhibits excellent electrochemical performances, delivering a discharge voltage platform of ∼2.91 V and a charge voltage platform of ∼3.52 V at 0.1 mA cm −2, showing a good cycle performance and having a discharge capacity of ∼7150 mAh g −1 carbon+catalyst at 0.1 mA cm −2 . The excellent performance of the F-PNG electrode is attributed to the good catalytic activity of uniformly distributed extremely small Fe/Fe3 C particles and N-doped graphene, the high electronic conductivity, and the 3-D porous structure. These results indicate that F-PNG can be an excellent cathode material for Li–O2 batteries, and MOFs-assisted synthesis method would be a promising new strategy for the synthesis of 3-D porous graphene materials.